The Toxicity of Beauty Standards: Body Image Perception Among Women Acne Fighters - Aqilah, Najwa Salma; Trihandayani, Dewi (Bulletin of Counseling and Psychotherapy, 2024)
Beauty is often closely linked with physical appearance in the current digital era. Prevailing beauty standards in society presuppose certain criteria for beauty, making adherence to these standards the primary basis for assessing one's body image. This study aims to provide an overview of the body image perceptions among women who struggle with acne or "acne fighters." This qualitative research adopts a phenomenological design. Participants were purposively selected using the purposive sampling method. Data were collected through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). Findings indicate that women who are acne fighters are dissatisfied with their physical condition, depicting their appearance as unattractive and failing to meet prevailing beauty standards within their social environment. This dissatisfaction leads to decreased self-confidence and negative impacts on social relationships. The study also identifies that one of the main contributing factors to the formation of negative body image is the normalized beauty standards prevalent in society.